Implementasi program BTQ dalam meningkatkan kefasihan membaca Al-Qur’an siswa kelas vii di UPT SMPN 2 Gresik - Lailatul Ilmiyah; Mut Mainawati; Nurul Afifah; Imam Syafi'i; Bambang Sujianto; Mohammad Salim (Al-Liqo: Jurnal Pendidikan Islam, 2026)
BTQ program aims to improve students’ ability to read the Qur'an accurately in accordance with tajwid rules. This study examines the effectiveness of the BTQ program in enhancing the Qur'anic reading fluency of seventh-grade students at UPT SMP Negeri 2 Gresik. A qualitative field research approach was employed, with data collected through observation, interviews, and documentation. The findings indicate that the BTQ program was implemented effectively and contributed positively to students’ reading proficiency. Students demonstrated improvements in fluency, accuracy, and confidence when reading both Iqra' and the Qur'an. They also showed strong enthusiasm for participating in the learning activities. The instructional process involved guided reading sessions in which students read according to their proficiency level, while teachers provided immediate feedback on pronunciation, vowel length, and tajwid application. The effectiveness of the program was further analyzed using the implementation theory of Van Meter and Van Horn, revealing that the BTQ program achieved its intended objectives and supported students’ Qur'anic literacy development.